INGESTION OF ANTHROPIC WASTE IN OTARIA FLAVESCENS (CARNIVORA: OTARIIDAE) IN "SAN PEDRO" BEACH, LURIN, PERU - Torres-Zevallos, Uriel (2020)
Records documenting the ingestion of plastic anthropogenic wastes in marine mammals are almost non-existent in the Eastern Pacifi c. In the present work, the ingestion of a plastic net by the South American sea lion Otaria fl avescens (Shaw, 1800) in the “San Pedro” Beach, Lurín, Lima, Peru is reported. Necropsy of the specimen showed the presence of whitish plastic fi laments (nylon) (≈ 0.5 mm in diameter) intermixed with individuals of Mugil cephalus Linnaeus, 1758. Previous documentation in research/dissemination articles on ingestion of plastic anthropic macro-waste in this species in Peru has not been reported, nor in articles of international review. With this new report, 42.85% (n = 6) of the otarid species around the world have ingested plastic macro-waste.